Developing Scalable and Transparent Benefit Payment Systems in Myanmar - Stokkel, Inge (World Bank, Washington, DC, 2015)
Similar to other low-income countries, in Myanmar social protection benefits are usually provided through direct cash or food distribution. With the rapid development of the financial and telecommunications market in the country, there is the potential for a gradual transition to electronic payment systems for current and future social protection transfers, once adequate legal and regulatory frameworks are in place. This will make the delivery of payments cheaper, quicker, safer, and more transparent. In addition, increasing the connectivity of the people of Myanmar, especially the poor and vulnerable, to financial services will not only accelerate povertyreduction but also promote inclusive economic growth.